The Influence of Academic Service Quality on Student Satisfaction and Achievement at Muhammadiyah 2 Alternative Elementary School in Magelang City: Pengaruh Kualitas Layanan Akademik Terhadap Kepuasan dan Prestasi Peserta Didik di SD Mutual 2 Kota Magelang - Chamsin, Edi; Asriningsih, Fauziah (Prosiding University Research Colloquium, 2023)
This study aims to determine (1) the quality of academic services, (2) the level of student satisfaction, (3) the level of student achievement, (4) the influence of academic services on student satisfaction, (5) the influence of the quality of academic services on student achievement, (6) the effect of satisfaction on student achievement, and (7) the influence of the quality of academic services on student achievement through student satisfaction. This research uses a descriptive-correlational quantitative approach method. In this study, the population was 90 students. Sampling using purposive sampling techniques and startifien sampling obtained 36 respondents. Statement questionnaires are used to collect data. Then for data analysis using path analysis. The results showed that: (1) the level of academic service quality was in the very good category, (2) the level of student satisfaction was in the very satisfied category, (3) student achievement was in the good category, (4) there was no significant effect on quality academic services on student satisfaction, (5) there is a significant effect of academic services on student achievement, (6) there is a significant effect between satisfaction on student achievement, and (7) there is a low significant effect of the quality of academic services on student achievement students through the variables of student satisfaction at SD Muhammadiyah 2 Alternative Magelang City.